Somatic Hypermutation Defects in Common Variable Immune Deficiency - Almejún, María Belén (2017)
Common variable immunodeficiency (CVID) is a heterogeneous disorder characterized by impaired antibody production and recurrent infections. In the last 20 years, several groups have reported that B cells from CVID patients have an impaired somatic hypermutation (SHM). The reported frequency of this defect among CVID patient cohorts is highly variable and so is the methodology used to evaluate this process. Interestingly, the low level of SHM on B cells from CVID patients has been correlated with the presence of infectious and non-infectious complications. In this review, an overview of the studies regarding SHM in CVID patients is presented. We highlight the importance of SHM studies in CVID patients as a clinical tool due to the reported association with clinical complications by several groups. We also considered SHM measurement useful to guide future investigations in order to identify genetic defects involved in the development of the disease.